ASSESSMENT OF WATER QUALITY IN CHLORINATED DRINKING WATER DISTRIBUTION NETWORKS REGARDING TO TRIHALOMETHANES FORMATION - Hanan Hosni Badr; Ali Abdel Rahman Gad; Ahmed Farghaly (JES: Journal of Engineering Sciences, 2022)
Chlorine disinfection in conventional water treatment plants in Egypt is a popular and inexpensive technique for disinfecting raw surface water before distribution to consumers. Nevertheless, the chlorination process in the presence of natural organic matter and decreased water quality due to uncontrollable population results in formation of high concentrations of carcinogenic disinfection by-products, from which trihalomethanes (THMs). In this paper, the water quality of Assiut drinking water network (ADWN) was assessed in terms of THMs studying different water quality parameters. An extended period simulation based on a modelling software WaterGEMS was employed to obtain the critical locations to be examined according to key parameters namely: water age, residual chlorine concentration, water velocity, and type of storage. The study concluded that THMs concentrations from all critical locations in Assiut drinking water network would not exceed the Egyptian regulatory threshold and US Environmental Protection Agency (EPA) guidelines. Even more, an investigated domestic roof tank should be critically operated under a planned scheme of monitoring and maintenance due to its deteriorated water quality.